The Arginine Residue within the C-Terminal Active Core of Bombyx mori Pheromone Biosynthesis-Activating Neuropeptide is Essential for Receptor Binding and Activation - Kawai, Takeshi; LEE, JaEMin; Nagata, Koji; Matsumoto, Shogo; Tanokura, Masaru; Nagasawa, Hiromichi (Frontiers in Endocrinology, 2012)
In most lepidopteran insects, the biosynthesis of sex pheromones is regulated by pheromone biosynthesis activating neuropeptide (PBAN). Bombyx mori PBAN (BomPBAN) consists of 33 amino acid residues and contains a C-terminus FSPRLamide motif as the active core. Among neuropeptides containing the FXPRLamide motif, the arginine (Arg, R) residue two positions from the C-terminus is highly conserved across several neuropeptides, which can be designated as RXamide peptides. The purpose of this study was to reveal the role of the Arg residue in the BomPBAN active core. We synthesized a ten-residue peptide corresponding to the C-terminal part of BomPBAN with a series of point mutants at the 2nd position (ie, Arg) from the C-terminus, termed the C2 position, and measured their efficacy in stimulating Ca2+ influx in insect cells concomitantly expressing a fluorescent PBAN receptor chimera (PBANR-EGFP) and loaded with the fluorescent Ca2+ indicator, Fura Red-AM. PBAN analogs with the C2 position replaced with alanine (Ala, A), aspartic acid (Asp, D), serine (Ser, S) or L-2-aminooctanoic acid (Aoc) decreased PBAN-like activity. RC2A (SKTRYFSPALamide) and RC2D (SKTRYFSPDLamide) had the lowest activity and could not inhibit the activity of PBAN C10 (SKTRYFSPRLamide). We also prepared Rhodamine Red-labeled PBAN analogs of the mutants and examined their ability to bind PBANR. In contrast to 100 nM Rhodamine Red-PBAN C10, none of the mutants at the same concentration exhibited PBANR binding. Taken together, our results demonstrate that the C2 Arg residue in BomPBAN is essential for PBANR binding and activation.